Preparation method of high-silicon Y-type molecular sieve
By using a mixed solution of sodium metaaluminate solution, sodium hydroxide and deionized water and superstable Y molecular sieve for primary crystallization in the preparation process of high-silicon Y molecular sieve, combined with a guide solution of water glass and sodium metaaluminate solution, the high-silicon Y molecular sieve is efficiently prepared under the conditions of low feed silicon-aluminum ratio, and the problems of low silicon source utilization and long crystallization time in the prior art are solved.
Patent Information
- Application Number
- CN202411867171.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-12-18
AI Technical Summary
In the preparation of high-silicon Y-type molecular sieve, the feeding silicon-aluminum ratio is high, the silicon source utilization rate is low, the skeleton silicon-aluminum ratio is limited, the crystallization time is long, the process flow is complex, and the need for additional organic matter is required.
The mixed solution of sodium metaaluminate solution, sodium hydroxide and deionized water is used to crystallize with the ultra-stable Y molecular sieve to prepare a seed gel; then it is allowed to stand in the water glass, sodium metaaluminate solution and water guide solution to form a guide solution; then heat and stir in the reaction system of silicon powder, alkali source and deionized water, add aluminate and sodium metaaluminate solution to form a reaction gel, and add seed gel and guide solution to undergo aging treatment and secondary crystallization, and finally prepare a high silicon Y-type molecular sieve.
The silicon source utilization rate of the synthetic system is significantly improved, and the high-silicon Y-type molecular sieve is directly synthesized under the conditions of low feed silicon-aluminum feed ratio, shortening the crystallization time, simplifying the process flow, and reducing the dependence on organic matter.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of molecular sieve synthesis and relates to a preparation method of a high-silicon Y-type molecular sieve. Background Art
[0002] The Y-type molecular sieve has a FAU framework topology and a super cage structure formed by β cages, and its pore size is about 0.74nm. When the framework silicon-aluminum ratio of the NaY molecular sieve (hereinafter referred to as the SiO2 / Al2O3 molar ratio) is greater than 6, it is called a high-silicon Y molecular sieve, which often has stronger hydrothermal stability, catalytic activity and adsorption performance. Therefore, the high-silicon Y molecular sieve has a wider range of applications in the fields of catalysis, adsorption purification and separation.
[0003] The preparation of high-silicon Y molecular sieves is mainly done by direct synthesis and secondary synthesis. The secondary synthesis method requires multiple high-temperature hydrothermal or high-temperature gas phase reactions to dealuminate and replenish silicon on conventional NaY molecular sieves, which can easily cause a serious decrease in the crystallinity of the molecular sieve. In addition, the process is cumbersome, energy-intensive, and highly polluting. Compared with the secondary synthesis method, the direct synthesis method has simple steps, high efficiency, and low pollution, and has become a research hotspot for the preparation of high-silicon Y molecular sieves.
[0004] At present, the direct synthesis method is mainly a template method and a template-free method. The template method needs to add expensive crown ethers, imidazoles or organic ammonium substances as templates in the preparation system, which significantly increases the production cost and causes large pollution, which is not conducive to large-scale industrial production. The template-free method has a simple process, low production cost, low environmental pollution, and better industrial application prospects. In 1972, Grace Company of the United States proposed for the first time in US3639099 to use water glass as a silicon source and add a crystallization directing agent to the synthesis system to prepare a Y molecular sieve, but the prepared Y molecular sieve skeleton silicon-aluminum ratio was lower than 5.2. Thereafter, researchers improved the method for preparing high-silicon Y molecular sieves by the template-free method on this basis. CN108569705B adds an organosiloxane as a promoter to the directing agent and the reaction gel, and prepares a high-silicon Y molecular sieve with a silicon-aluminum ratio of 5.5 to 6.5 after aging for 12 to 192 hours and crystallization for 18 to 72 hours when the silicon-aluminum ratio of the feed is 7 to 10. CN110078084B uses high-activity silicon source obtained by high-temperature treatment of solid silicic acid, microsphere silica gel or white carbon black and polymer as raw materials, and prepares a high silicon Y molecular sieve with a silicon-aluminum ratio of 5.5 to 7.0 by adding a guiding agent and aging for 24 to 180 hours at a feed silicon-aluminum ratio of 7.5 to 10.5, and crystallizing for 2 to 24 hours. CN101468804B introduces ester or alcohol additives into the system of adding a guiding agent, and prepares a high silicon Y molecular sieve with a silicon-aluminum ratio of 5.5 to 6.0 after crystallization for 10 to 55 hours at a feed silicon-aluminum ratio of 6 to 10. CN101767799B uses water glass as a silicon source, and synthesizes a high silicon Y molecular sieve with a silicon-aluminum ratio higher than 6.0 and a grain size of 50 to 150 nm by adding a guiding agent prepared by aging at 0 to 10°C for 50 to 120 hours at a feed silicon-aluminum ratio of 6 to 10. CN1033503C obtains an improved guiding agent with a transmittance of >75% by adding a silicon source to a conventional guiding agent, and obtains a Y molecular sieve with a silicon-aluminum ratio of 5.8 by conventional hydrothermal treatment under the condition that the silicon-aluminum ratio of the feed is higher than 12. CN102198950B uses water glass as the silicon source, prepares gels of different proportions, and crystallizes them separately for more than 16 hours, then mixes and recrystallizes them for more than 24 hours to obtain a high-silicon Y molecular sieve with a silicon-aluminum ratio of 5.6 to 6.2. CN103896303B uses water glass as the silicon source, adds a guiding agent to the system, and obtains a high-silicon Y molecular sieve with a silicon-aluminum ratio higher than 6.5 and an average particle size of 100 to 500 nm through three-stage dynamic crystallization under the condition that the silicon-aluminum ratio of the feed is 10 to 25. CN101251929B uses water glass as raw material, prepares high-basicity silica-alumina gel with a silicon-alumina ratio of 8 to 15, crystallizes for a period of time, then adds low-basicity silica-alumina gel to continue crystallization to prepare a high-silicon Y molecular sieve with a silicon-alumina ratio of 5.5 to 6.0.
[0005] In summary, although the current technology for directly preparing high-silicon Y molecular sieves can improve the silicon-aluminum ratio of the product, it still has disadvantages such as high feed silicon-aluminum ratio, low silicon source utilization, limited improvement in the framework silicon-aluminum ratio, long crystallization time, complex process flow, and the need for additional addition of organic matter. Therefore, it is urgent to study a simple and efficient high-silicon Y molecular sieve preparation process. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a high-silicon Y-type molecular sieve, which can significantly improve the silicon source utilization rate of the synthesis system, can directly synthesize the high-silicon Y-type molecular sieve under the condition of a lower feed silicon-aluminum ratio, and greatly shorten the crystallization time.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] A method for preparing a high-silicon Y-type molecular sieve, characterized in that it comprises the following steps:
[0009] S1, mixing a sodium aluminate solution, sodium hydroxide and deionized water, then adding ultra-stable Y molecular sieve (abbreviated as ultra-stable Y) to the mixed solution, stirring evenly, and once crystallizing to obtain a seed gel;
[0010] S2, mixing water glass, sodium aluminate solution and water in a molar ratio of SiO2:Al2O3:Na2O:H2O=15-20:1:15-20:280-360, standing and aging to obtain a directing agent solution;
[0011] S3, mixing silicon powder, alkali source and deionized water under heating and stirring for a reaction, then adding aluminate, sodium metaaluminate solution and deionized water to mix to obtain a reaction gel, and then continuing to add the seed gel in S1 and the directing agent solution in S2, mixing evenly and then passing direct current for aging treatment;
[0012] S4, subjecting the aged material to an aging treatment, and then transferring it to a crystallization kettle for secondary crystallization to obtain a high-silicon Y-type molecular sieve.
[0013] Furthermore, in S1, the added amounts of sodium aluminate solution, sodium hydroxide and deionized water satisfy: Al2O3:Na2O:H2O=1:8~25:100~350. It should be pointed out here that Al2O3:Na2O:H2O is a measurement form only for the convenience of calculating the ratio of different components, and does not mean that the components in the solution exist as "Al2O3, Na2O", etc. This is common knowledge in the art, the same below.
[0014] The weight ratio of the mixed solution to the ultra-stable Y molecular sieve is 2 to 10:1.
[0015] Furthermore, in S1, the temperature of the first crystallization is 70 to 120° C., and the crystallization time is 2 to 8 hours.
[0016] Further, in S1, the ultrastable Y molecular sieve is a Y-type molecular sieve with a high silicon-aluminum ratio, and its framework silicon-aluminum ratio is higher than 20. It can specifically adopt conventional commercial products that meet this limited condition in the art, and since the specific source does not belong to the innovation of the present invention, it will not be repeated here.
[0017] Furthermore, in S2, the temperature of the static aging is from room temperature to 60°C, and the time is 12 to 48 hours.
[0018] Further, in S3, the molar ratio of silicon powder, alkali source and deionized water is 1:0.6-0.8:7-13;
[0019] The temperature of a primary reaction is 50-70°C and the time is 3-8 hours. Preferably, the alkali source is one or more of NaOH, KOH or ammonia water, and more preferably, the alkali source is NaOH.
[0020] Furthermore, the metal silicon powder is 150-500 mesh, and the silicon content is higher than 97.0%.
[0021] Furthermore, in S3, the addition amounts of aluminate, sodium aluminate solution and deionized water satisfy the following conditions: SiO2:Al2O3:M x O:H2O=5~12:1:0.5~4:80~300, the amount of seed gel added accounts for 1~15wt% of the mass of the reaction gel, and the amount of directing agent solution added accounts for 1~15wt% of the mass of the reaction gel. Preferably, the aluminate is one or more of aluminum sulfate, aluminum chloride or aluminum nitrate, and aluminum sulfate is further preferred. Specifically, M includes Na and other alkaline metal cations that may be contained in the alkali source. For example, when the alkali source is sodium hydroxide, M is Na; and when the alkali source is KOH, M includes Na and K.
[0022] Furthermore, in S3, during the aging process, the current density of the DC current is 50-100 mA / cm 2 , the processing time is 0.5 to 3 hours.
[0023] Furthermore, in S4, the aging treatment temperature is room temperature to 60° C., and the aging time is 2 to 12 hours.
[0024] Furthermore, in S4, the temperature of the secondary crystallization is 80 to 120° C., and the crystallization time is 6 to 30 hours.
[0025] Compared with the prior art, the present invention has the following advantages:
[0026] 1. The present invention utilizes the reaction of metallic silicon powder and alkaline solution in the synthesis process to prepare a highly active silicon source, whose silicate polymerization degree is low and concentrated, and which is more easily dissolved, polymerized and rearranged in a low-alkalinity reaction system, accelerating the generation of crystal nuclei, thereby improving the utilization rate of the silicon source.
[0027] 2. The present invention introduces an incompletely crystallized seed gel into the crystallization system, and uses ultra-stable Y as the silicon source. Because of its high skeleton silicon content, after a short period of incomplete crystallization, the gel contains a large number of uncrystallized high-silicon nuclei and scattered high-silicon secondary structural unit fragments, which play a certain guiding role in the synthesis of high-silicon Y-type molecular sieves, improve the silicon-aluminum ratio of the Y molecular sieve skeleton, and accelerate the crystallization process.
[0028] 3. The present invention introduces direct current into the crystallization system. The hydroxyl radicals generated by electrolysis can promote the depolymerization and reconstruction of polysilicates. In the nucleation stage, the presence of hydroxyl radicals can accelerate the self-assembly polymerization rearrangement process of Si-O-Si bonds around the crystal nucleus or secondary structural units, thereby improving the framework silicon-aluminum ratio of the Y molecular sieve.
[0029] 4. The present invention has simple steps, can reduce the alkalinity of the system, and improve the utilization rate of the silicon source, so as to realize the rapid preparation of high-silicon Y-type molecular sieve under the condition of low feed silicon-aluminum ratio. DETAILED DESCRIPTION
[0030] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0031] In the following examples, the unit cell constant of NaY molecular sieve is determined by X-ray diffraction. First, the unit cell constant a of Y zeolite is determined according to the standard method of SH / T0339-92; then the silicon-aluminum ratio of NaY molecular sieve is calculated according to the Breck-Flanigen formula: SiO2 / Al2O3=2(25.858-a) / (a-24.191).
[0032] In addition, the ultra-stable Y used in this embodiment is purchased from Fuyu (Zhangjiagang) New Materials Co., Ltd., and the corresponding models of different silicon-aluminum ratios in Examples 1 to 3 are SAR-30, SAR-60, and SAR-20, respectively. Of course, in the following embodiments, other commercially available products can also be used, and under the condition of meeting the same silicon-aluminum ratio, there is basically no effect on the performance of the final product.
[0033] The rest of the raw materials or processing techniques, unless otherwise specified, are conventional commercially available raw materials or conventional processing techniques in the art.
[0034] Embodiment 1:
[0035] Preparation of seed gel: According to the molar ratio of Al2O3:Na2O:H2O=1:15:200, 10.0g NaOH was weighed and dissolved in 26.2g deionized water. After stirring, 12.4g sodium aluminate solution (wherein the Na2O concentration is 12.43%, the Al2O3 concentration is 8.25%, the same below) was added and stirred evenly. Then, 8.1g of ultra-stable Y with a framework silicon-aluminum ratio of 30 was added according to the ratio of mixed solution: ultra-stable Y=6:1. After stirring for 2h, crystallize at 90°C for 3h to obtain a seed gel.
[0036] Preparation of guiding agent solution: weigh 7.2g NaOH and dissolve it in 24.0g deionized water, then add 12.4g sodium aluminate solution, and finally add 35.7g conventional 3.2M water glass (SiO2 content is 25.2%, Na2O content is 8.1%), stir evenly, and age at 30°C for 24h to obtain a guiding agent solution, in which the molar ratio of the composition is SiO2:Al2O3:Na2O:H2O=15:1:16:320.
[0037] According to the molar ratio of metal silicon powder, NaOH and deionized water of 1:0.6:10.5, 4.9g NaOH was weighed and dissolved in 38.3g deionized water. After stirring at 60°C, 5.7g 200-mesh metal silicon powder was added and refluxed for 4h. After the reaction was completed, 5.7g aluminum sulfate 18hydrate, 20.4g sodium aluminate solution and 31.5g deionized water were added thereto and stirred until uniform. The molar ratio of the composition was SiO2:Al2O3:Na2O:H2O=8:1:2.0:180. 10.0g seed gel and 10.0g directing agent solution were added according to 8% of the weight of the reaction gel, respectively, and stirred until uniform. Then, a current density of 80mA / cm 2 The treated reaction gel was aged at 50℃ for 6h and then transferred to a crystallization kettle for crystallization at 100℃ for 24h. After the reaction, it was filtered, washed and dried to obtain a Y-type molecular sieve. XRD measured its silicon-aluminum ratio to be 6.5 and the relative crystallinity to be 97%.
[0038] Example 2
[0039] The preparation of the directing agent solution is the same as that in Example 1.
[0040] Preparation of seed gel: According to the molar ratio of Al2O3:Na2O:H2O=1:20:150, 14.2g NaOH was weighed and dissolved in 17.2g deionized water. After stirring evenly, 12.4g sodium aluminate solution was added and stirred evenly. Then, 10.9g ultra-stable Y with a framework silicon-aluminum ratio of 60 was added according to the ratio of mixed solution: ultra-stable Y=4:1. After stirring evenly for 2h, it was crystallized at 110°C for 3h to obtain a seed gel.
[0041] According to the molar ratio of metal silicon powder, KOH and deionized water of 1:0.8:13, 6.7g KOH was weighed and dissolved in 35.2g deionized water, and after stirring at 70°C, 4.2g of 200-mesh metal silicon powder was added, and refluxed for 6h. After the reaction was completed, 13.3g of aluminum sulfate 18hydrate, 6.2g of sodium aluminate solution and 4.1g of deionized water were added thereto, and stirred until uniform. The molar ratio of the composition was SiO2:Al2O3:(Na2O+K2O):H2O=6:1:1.0:90. According to 10% of the weight of the reaction gel, 7.0g of seed gel was added, and according to 3.0% of the weight of the reaction gel, 2.1g of the directing agent solution was added, and stirred until uniform, and then a current density of 90mA / cm 2 The treated reaction gel was aged at 50℃ for 8h and then transferred to a crystallization kettle for crystallization at 100℃ for 24h. After the reaction, it was filtered, washed and dried to obtain a Y-type molecular sieve. XRD measured its silicon-aluminum ratio to be 5.6 and the relative crystallinity to be 93%.
[0042] Example 3
[0043] The preparation of the directing agent solution is the same as in Example 1.
[0044] Preparation of seed gel: According to the molar ratio of Al2O3:Na2O:H2O=1:10:300, 6.1g NaOH was weighed and dissolved in 44.2g deionized water. After stirring evenly, 12.4g sodium aluminate solution was added and stirred evenly. Then, 7.8g ultra-stable Y with a framework silicon-aluminum ratio of 20 was added according to the ratio of mixed solution: ultra-stable Y=8:1. After stirring evenly for 2h, it was crystallized at 80°C for 6h to obtain a seed gel.
[0045] According to the molar ratio of metal silicon powder, alkali source and deionized water of 1:0.6:7, 4.0g NaOH was weighed and dissolved in 29.1g deionized water, 3.4g ammonia water with a concentration of 25% was added and stirred at 50°C, and then 7.0g 500-mesh metal silicon powder was added. The reaction was refluxed for 8h. After the reaction was completed, 3.0g aluminum sulfate 18hydrate, 25.4g sodium aluminate solution and 65.6g deionized water were added thereto and stirred until uniform. The molar ratio of the composition was SiO2:Al2O3:Na2O:H2O=10:1:3.0:250. 4.1g seed gel was added according to 3.0% of the weight of the reaction gel, and 13.8g directing agent solution was added according to 10.0% of the weight of the reaction gel. The mixture was stirred until uniform, and then a current density of 60mA / cm was passed. 2 The treated reaction gel was aged at 40℃ for 8h and then transferred to a crystallization kettle for crystallization at 100℃ for 12h. After the reaction, it was filtered, washed and dried to obtain a Y-type molecular sieve. XRD measured its silicon-aluminum ratio to be 7.1 and the relative crystallinity to be 94%.
[0046] Example 4
[0047] The preparation of the directing agent solution and the seed gel is the same as in Example 1.
[0048] According to the molar ratio of metal silicon powder, alkali source and deionized water of 1:0.7:9, 6.3g NaOH was weighed and dissolved in 36.0g deionized water. After stirring at 60°C, 6.3g 200-mesh metal silicon powder was added and refluxed for 3h. After the reaction was completed, 8.3g aluminum sulfate 18hydrate, 15.6g sodium aluminate solution and 24.4g deionized water were added thereto and stirred until uniform. The molar ratio of the composition was SiO2:Al2O3:Na2O:H2O=9:1:1.5:150. 6.7g seed gel was added according to 8.0% of the weight of the reaction gel. 6.7g directing agent solution was added according to 8.0% of the weight of the reaction gel. The mixture was stirred until uniform. Then a current density of 75mA / cm was introduced. 2 The treated reaction gel was aged at 60℃ for 4h and then transferred to a crystallization kettle for crystallization at 100℃ for 24h. After the reaction, it was filtered, washed and dried to obtain a Y-type molecular sieve. XRD measured its silicon-aluminum ratio to be 7.3 and the relative crystallinity to be 99%.
[0049] Comparative Example 1
[0050] The preparation method of the directing agent is the same as that of Example 1.
[0051] The preparation method of the reaction gel is the same as that of Example 1, but no seed gel is added to the reaction gel.
[0052] The details are as follows:
[0053] According to the molar ratio of metal silicon powder, NaOH and deionized water of 1:0.6:10.5, 4.9g NaOH was weighed and dissolved in 38.3g deionized water. After stirring at 60°C, 5.7g 200-mesh metal silicon powder was added and refluxed for 4h. After the reaction was completed, 5.7g aluminum sulfate 18hydrate, 20.4g sodium aluminate solution and 31.5g deionized water were added thereto and stirred until uniform. The molar ratio of the composition was SiO2:Al2O3:Na2O:H2O=8:1:2.0:180. According to 8% of the weight of the reaction gel, 10.0g of the directing agent solution was added and stirred until uniform. Then, a current density of 80mA / cm was passed. 2 The treated reaction gel was aged at 50℃ for 6h and then transferred to a crystallization kettle for crystallization at 100℃ for 24h. After the reaction, it was filtered, washed and dried to obtain a Y-type molecular sieve. XRD measured its silicon-aluminum ratio to be 5.9 and the relative crystallinity to be 95%.
[0054] Comparative Example 2
[0055] The preparation method of the directing agent is the same as that of Example 1.
[0056] The preparation method of the reaction gel is the same as that of Example 1, but no direct current is introduced during the preparation process. The details are as follows:
[0057] According to the molar ratio of metal silicon powder, NaOH and deionized water being 1:0.6:10.5, 4.9g NaOH was weighed and dissolved in 38.3g deionized water, and after being stirred at 60°C, 5.7g 200-mesh metal silicon powder was added, and the mixture was refluxed for 4h. After the reaction was completed, 5.7g aluminum sulfate 18hydrate, 20.4g sodium aluminate solution and 31.5g deionized water were added thereto, and the mixture was stirred until uniform. The molar ratio of the composition was SiO2:Al2O3:Na2O:H2O=8:1:2.0:180. According to 8% of the weight of the reaction gel, 10.0g seed gel was added, and according to 8% of the weight of the reaction gel, 10.0g directing agent solution was added, and the mixture was stirred until uniform. The reaction gel was aged at 50°C for 6h, and then transferred to a crystallization kettle and crystallized at 100°C for 24h. After the reaction was completed, the mixture was filtered, washed and dried to obtain a Y-type molecular sieve. XRD measured its silicon-aluminum ratio to be 5.7 and its relative crystallinity to be 97%.
[0058] Comparative Example 3
[0059] The preparation method of the directing agent and the seed gel is the same as that of Example 1
[0060] The preparation method of the reaction gel is the same as that of Example 1. However, the silicon source in the preparation process is conventional 3.2M water glass, whose SiO2 content is 25.2% and Na2O content is 8.1%. The details are as follows:
[0061] Weigh 47.6g of conventional 3.2M water glass, add 4.0g of aluminum sulfate 18hydrate, 23.5g of sodium aluminate solution and 30.6g of deionized water, stir until uniform, the molar ratio of the composition is SiO2:Al2O3:Na2O:H2O=8:1:2.0:180, add 8.5g of seed gel according to 8% of the weight of the reaction gel, add 8.5g of directing agent solution according to 8% of the weight of the reaction gel, stir until uniform, stir until uniform, and then pass a current density of 80mA / cm 2 The treated reaction gel was aged at 50℃ for 6h and then transferred to a crystallization kettle for crystallization at 100℃ for 24h. After the reaction, it was filtered, washed and dried to obtain a Y-type molecular sieve. XRD measured its silicon-aluminum ratio to be 5.7 and the relative crystallinity to be 92%.
[0062] Comparative Example 4
[0063] The preparation method of the directing agent is the same as that of Example 1, and the composition ratio of the reaction gel is the same as that of Example 1.
[0064] Conventional 3.2M water glass was used as the silicon source (SiO2 content was 25.2%, Na2O content was 8.1%), and Y-type molecular sieve was prepared according to the conventional directing agent method. The details are as follows:
[0065] Weigh 47.6g of conventional 3.2M water glass, add 4.0g of aluminum sulfate 18hydrate, 23.5g of sodium aluminate solution and 30.6g of deionized water, stir until uniform, the molar ratio of the composition is SiO2:Al2O3:Na2O:H2O=8:1:2.0:180, add 8.5g of directing agent solution according to 8% of the weight of the reaction gel, stir until uniform, age the reaction gel at 50℃ for 6h, transfer it to a crystallization kettle and crystallize it at 100℃ for 24h, filter, wash and dry after the reaction to obtain Y-type molecular sieve. XRD measured its silicon-aluminum ratio of 5.2 and relative crystallinity of 95%.
[0066] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a high-silicon Y-type molecular sieve, characterized in that: The following steps are involved: S1, mixing sodium aluminate solution, sodium hydroxide and deionized water, then adding ultra-stable Y molecular sieve to the mixed solution, stirring evenly, and once crystallizing to obtain a seed gel; S2, mixing water glass, sodium aluminate solution and water in a molar ratio of SiO2:Al2O3:Na2O:H2O=15-20:1:15-20:280-360, standing and aging to obtain a directing agent solution; S3, mixing silicon powder, alkali source and deionized water under heating and stirring for a reaction, then adding aluminate, sodium metaaluminate solution and deionized water to mix to obtain a reaction gel, and then continuing to add the seed gel in S1 and the directing agent solution in S2, mixing evenly and then passing direct current for aging treatment; S4, subjecting the aged material to an aging treatment, and then transferring it to a crystallization kettle for secondary crystallization to obtain a high-silicon Y-type molecular sieve.
2. The method for preparing a high-silicon Y-type molecular sieve according to claim 1, characterized in that: In S1, the addition amounts of sodium aluminate solution, sodium hydroxide and deionized water satisfy: Al2O3:Na2O:H2O=1:8-25:100-350; The weight ratio of the mixed solution to the ultra-stable Y molecular sieve is 2 to 10:
1.
3. The method for preparing a high-silicon Y-type molecular sieve according to claim 1, characterized in that: In S1, the primary crystallization temperature is 70 to 120° C., and the crystallization time is 2 to 8 hours.
4. The method for preparing a high-silicon Y-type molecular sieve according to claim 1, characterized in that: In S1, the framework silicon-aluminum ratio of the ultrastable Y molecular sieve is higher than 20.
5. The method for preparing a high-silicon Y-type molecular sieve according to claim 1, characterized in that: In S2, the temperature of static aging is from room temperature to 60°C, and the time is 12 to 48 hours.
6. The method for preparing a high-silicon Y-type molecular sieve according to claim 1, characterized in that: In S3, the molar ratio of silicon powder, alkali source and deionized water is 1:0.6-0.8:7-13; The temperature of a single reaction is 50-70°C and the time is 3-8 hours; The alkali source is one or more of NaOH, KOH or ammonia water.
7. The method for preparing a high-silicon Y-type molecular sieve according to claim 1, characterized in that: In S3, the addition amount of aluminate, sodium aluminate solution and deionized water satisfies the following conditions: SiO2:Al2O3:M x O:H2O=5-12:1:0.5-4:80-300, the amount of seed gel added accounts for 1-15wt% of the mass of the reaction gel, the amount of directing agent solution added accounts for 1-15wt% of the mass of the reaction gel, and M includes Na and alkaline metal cations contained in the alkali source; The aluminate is one or more of aluminum sulfate, aluminum chloride or aluminum nitrate.
8. The method for preparing a high-silicon Y-type molecular sieve according to claim 1, characterized in that: In S3, during the aging process, the current density of the DC current is 50-100 mA / cm 2 , the processing time is 0.5 to 3 hours.
9. The method for preparing a high-silicon Y-type molecular sieve according to claim 1, characterized in that: In S4, the aging treatment temperature is room temperature to 60° C., and the aging time is 2 to 12 hours.
10. The method for preparing a high-silicon Y-type molecular sieve according to claim 1, characterized in that: In S4, the temperature of the secondary crystallization is 80 to 120° C., and the crystallization time is 6 to 30 hours.
Citation Information
Patent Citations
Method for preparing NaY molecular sieve with high silica-alumina ratio and product thereof
CN104692413A
Preparation method of high-purity nano silica sol with controllable particle size
CN117049553A
Method for forming zeolite thin film, and zeolite thin film
JP2008050223A
Method of preparing hierarchical porous channel molecular sieve membrane and application thereof
US20190262779A1